The Role of Hadith in Building Entrepreneurial Mentality - Mohammad Husaini; Ahmad Mohammad Tidjani (Values: Jurnal Kajian Islam Multidisiplin, 2024)
This research aims to explore the role of hadith in building an entrepreneurial mentality based on Islamic values through a literature review. The hadiths of the Prophet Muhammad (SAW) provide guidance on ethics, morals, and the spirit of entrepreneurship, such as honesty, hard work, innovation, and the courage to take risks. The research method used is a literature review, analyzing primary hadith collections and contemporary literature related to entrepreneurship in Islam. The results show that the entrepreneurial values found in the hadiths are not only relevant but also provide solutions to the challenges of modern business ethics. Hadith plays a role in shaping the entrepreneurial mentality of Muslims, focusing on economic success while maintaining spiritual values and social responsibility. This study provides practical recommendations for integrating the values of hadith into entrepreneurship education and modern business practices to create a generation of competent and ethical Muslim entrepreneurs